2007
DOI: 10.1007/s10620-007-9887-0
|View full text |Cite
|
Sign up to set email alerts
|

The Activity of RhoA is Correlated with Lymph Node Metastasis in Human Colorectal Cancer

Abstract: Rho family GTPases play a pivotal role in the regulation of numerous cellular functions associated with malignant transformation and metastasis. To evaluate the role of these GTPases in colorectal cancer, the protein expression levels and activities of these proteins in matched sets of tumor and non-tumor tissues of surgical specimens were analyzed. The relationship between the protein levels and activities in tumor tissues to the clinicopathological features was also assessed. The expression levels of RhoA, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…RhoA overexpression has been identified in a variety of other cancers, and RhoA activity has been linked to tumorigenesis and invasion (31, 32). For example in colorectal cancer, increased RhoA expression in primary tumors correlates with lymph node metastasis and liver metastasis (33, 34). Fairly little is known about the role of RhoA in gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…RhoA overexpression has been identified in a variety of other cancers, and RhoA activity has been linked to tumorigenesis and invasion (31, 32). For example in colorectal cancer, increased RhoA expression in primary tumors correlates with lymph node metastasis and liver metastasis (33, 34). Fairly little is known about the role of RhoA in gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…30–33 However, the role of RhoA in gastric cancer tumorigenesis is poorly understood. Pan et al evaluated mRNA levels of the seven main members of the Rho GTPase family, including RhoA, in 53 gastric carcinoma tumor samples as well as seven gastric cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…RhoA inactivation was shown to reduce infiltration and metastases in both in vitro and in vivo experiments using pancreatic cancer cell lines [24]. Moreover, a recent study found that low immunohistological RhoA expression indicated a poor outcome in colorectal cancer [25]. Su et al [8] reported that RhoA expression was associated with deeper tumor invasion and a poor prognosis in gastric cancer.…”
Section: Discussionmentioning
confidence: 99%